Framing climate change as a generational issue: Experimental effects on youth worry, motivation and belief in collective action - Shane Timmons; Ylva Andersson; Pete Lunn (The Economic and Social Research Institute (ESRI), 2022)
Generations differ in their contribution to climate change and susceptibility to its effects. Framing climate change as an intergenerational issue may therefore alter public engagement. We report a pre-registered, online experiment with a youth sample (N = 500, aged 16-24 years) that tested whether framing climate change information in generational terms affects (i) worry about climate change, (ii) perception of others' worry, (iii) belief in collective action and (iv) pro-environmental intentions. We also tested the effect of correcting misperceptions about how concerned older people are. Generational framing amplified worry about climate change, with limited effects on other measures. Providing accurate information on older people's worry boosted belief in collective action, particularly for the majority who initially underestimated it. The results have implications for communications with young people about climate change.
Keywords: 330; climate change; young people; generations; social identity; framing; perception ofothers